VULNERABILITY OF A FISHERIES COMMUNITY UNDER THE INFORMAL ECONOMY: A CASE STUDY OF SENDANG BIRU, EAST JAVA - Sri Saptasari, Kiestiko (Jurnal Ilmiah Administrasi Publik, 2015)
Vulnerability of a Fisheries Community under the Informal Economy: A Case Study of Sendang Biru, East Java. This study is about fisheries communitiesâ livelihood that is highly vulnerable because of the informal economy. The main reason concerns about it is patron â client system between fishermen and middleman in their employment system. Other reasons related to educational background, seasonal type of work, unstable household income and loan depency, also exclusion to and/or from other community members in the village. The objectives of this research are to study the informal economic activities in fisheries communityâs livelihood, identify why fishermen are highly vulnerable, and provide information to increase government awareness as well as give consideration in making programs for fisheries community in Indonesia. This research applies qualitative technique based on field observations and in-depth interviews. For the conclusion, fishermenâs high dependency to middleman as their capital source, both for fishing activities and daily consumption needs, makes them highly vulnerable. Inspite of that, eliminating the role of middleman means taking out the only resources in their livelihood. Therefore, government should implement pro â fisherman assistances/ programs based on the real problems faced by the community.